Worth the wait - Foster, Lori, 1958- (Foster, Lori, 1958- Guthrie brothers., 2017)
Single dad Hogan Guthrie is getting his life back on track, and working as the “barbecue master” at a local café is just a temporary detour. He and restaurant owner Violet Shaw constantly butt heads<U+2026>until one night they end up mingling other parts instead. Hogan thought he had the recipe for happiness all figured out. But loyal, carefree Violet is daring him to trust his impulses<U+2026>and see just how sweet small-town living<U+2014>and loving<U+2014>can be. Nathan Hawley traded his SWAT team credentials for a sheriff's badge, but a gorgeous new neighbour is shaking up his orderly life. Nathan has a hunch there's more to Brooklin Sweet than meets the eye<U+2014>but given her caution about getting involved, he has his work cut out for him. Still, there's something about the elusive beauty Nathan can't walk away from<U+2014>and helping her come to terms with her past might pave the way to the future they both secretly long for.